Exporting democratic practices: Evidence from a village governance intervention in Eastern Congo - Macartan Humphreys; Raúl Sánchez de la Sierra; Peter Van der Windt (Journal of Development Economics, 2019)
We study a randomized Community Driven Reconstruction (CDR) intervention that provided two years of exposure to democratic practices in 1250 villages in eastern Congo. To assess its impact, we examine behavior in a village-level unconditional cash transfer project that distributed 1000 to 457 treatment and control villages. The unconditonal cash transfer provides opportunities to assess whetherpublic funds get captured, what governance practices are employed by villagers and village elites and whether prior exposure to the CDR intervention alters these behaviors. We find no evidence for such effects. The results cast doubt on current attempts to export democratic practices to local communities.
Keywords: D72; P48; D02; O17; 330; political processes; political economy; institutions; culture; demonstration effects